Exploring Indonesian Coffee: A Local Branding Strategy for Kopi Ratu Asih - Nadia Putri Yunizar; Khaerudin Imawan; Aghnia Dian Lestari (CONVERSE Journal Communication Science, 2026)
This study was motivated by the still-limited use of digital media and formal promotion by local coffee MSMEs in building their brand identity. Kopi Ratu Asih, a community-based local coffee brand in Cibeureum Village, Kuningan Regency, employs a branding strategy that focuses more on direct interaction, social relationships, and local values than on the use of digital promotional media. The purpose of this study is to see the application of Integrated Marketing Communication (IMC) elements in the Local Branding strategy of Kopi Ratu Asih. This study employed a qualitative case study approach by in-depth interviews with customers and members of the coffee community using the case study method. The findings indicate that the most dominant strategies in building a brand image and emotional closeness with consumers are the elements of personal selling, public relations and interactive marketing. Meanwhile, advertising and sales promotion have not been optimally applied, as Kopi Ratu Asih is more relies on marketing through community-based communication, word-of-mouth communication, and limited use of digital media as a medium to communicate with the community. Kopi Ratu Asih's brand is established by the quality of its product, the way people gather the coffee locally and the post-harvest processing, and the way people consume it with personal consumption experience and education.